Timbre Comparison in Note Tracking from Onset, Frames and Pitch Estimation - Hernández Oliván, Carlos; Zay Pinilla, Ignacio; Beltrán Blázquez, José Ramón (Jornada de Jóvenes Investigadores del I3A, 2020)
Note Tracking (NT) is a subtask of Automatic Music Transcription (AMT) which is a critical problem in the field of Music Information Retrieval (MIR). The aim of this work is to compare the performance of two models, one for onsets and frames prediction and another one with pitch detection and a note tracking algorithm in order to study the behaviour of different timbres and families of instruments in note tracking subtasks.